Comparing the antimicrobial impact of Artemisia afra, Erythrina lysistemon and Psidium guajava on Staphylococcus aureus, Escherichia coli and Pseudomonas aeruginosa - Nsele, Nhlanhla (Student's Journal of Health Research Africa, 2025)
Background and Significance Antimicrobial resistance has become a critical global health challenge, driving renewed interest in medicinal plants as potential sources of alternative therapies. Traditional South African medicinal plants, particularly Artemisia afra, Erythrina lysistemon, and Psidium guajava, have shown promise in preliminary studies but require systematic evaluation. Study Aim This study investigated the comparative antibacterial efficacy of these three plant species against clinically relevant pathogens: Staphylococcus aureus, Escherichia coli, and Pseudomonas aeruginosa. The research aimed to determine both the spectrum of activity and the influence of extraction solvents on antimicrobial potency. Materials and Methods Leaves of A. afra and P. guajava and bark of E. lysistemon were collected from Silverglen Nature Reserve. A modified German Homeopathic Pharmacopoeia protocol was employed to prepare both aqueous and 60% ethanolic extracts. Antimicrobial activity was evaluated using a standardized disk diffusion assay adapted from the Kirby-Bauer method, with subsequent minimum inhibitory concentration (MIC) determination for active extracts. Key Results The ethanolic extracts demonstrated selective antibacterial activity exclusively against S. aureus, with inhibition zones ranging from 6-14 mm. A. afra exhibited the strongest effect (12 mm), followed by P. guajava (10 mm) and E. lysistemon (8 mm). MIC analysis revealed P. guajava as the most potent, completely inhibiting S. aureus growth at 10.42 mg/mL. Notably, no activity was observed against Gram-negative pathogens (E. coli and P. aeruginosa), nor with aqueous extracts of any plant material. Conclusions and Implications These findings establish the Gram-positive-specific antibacterial properties of these traditional medicinal plants and highlight ethanol's superiority as an extraction solvent. The results provide scientific validation for certain ethnopharmacological uses while suggesting these plants as potential sources for developing narrow-spectrum antimicrobials. Future research should focus on compound isolation, mechanism of action studies, and potential synergies with existing antibiotics to address growing antimicrobial resistance challenges.